2018
DOI: 10.1111/ijn.12682
|View full text |Cite
|
Sign up to set email alerts
|

The effects of environmental factors in waiting rooms on anxiety among patients undergoing coronary angiography: A randomized controlled trial

Abstract: Environmental factors were shown to have a positive effect on the indices of anxiety experienced by patients waiting for the procedure of coronary angiography; this is therefore an area of study and practice worthy of further development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
1
13
1
1
Order By: Relevance
“…No doubt, the educated people have sufficient information about the procedure by inquiring it from the doctor or by searching on the internet and other media. This result agreed with Williams et al (2013); Re et al (2016); Gu et al (2016) and Delewi et al (2017) who reported that highly educated patients were with low rates of anxiety.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…No doubt, the educated people have sufficient information about the procedure by inquiring it from the doctor or by searching on the internet and other media. This result agreed with Williams et al (2013); Re et al (2016); Gu et al (2016) and Delewi et al (2017) who reported that highly educated patients were with low rates of anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…The present result may be due to that patients with a family history of cardiovascular diseases had sufficient knowledge and had prior experiences with their families regarding invasive procedures used in the diagnosis and treatment of coronary diseases and became familiar with the interventions with low anxiety level before coronary angiography and PCI. But, Ramesh et al (2017) in India found no correlation between the anxiety level and history family of heart disease.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…An appropriate context for the use of VR to reduce anxiety and improve mental wellbeing is in secondary care. Attending hospital is known to be stressful, and sitting in a waiting room can increase the anxiety in the patient awaiting examination or clinical procedure [11] [12]. Moreover, the time a patient spends waiting for an appointment offers researchers a chance to implement an intervention at an optimal moment without requiring the patient to make a separate visit to the health centre/ research location.…”
Section: Clinical Outcomes and Intervention Designmentioning
confidence: 99%
“…Οι ασθενείς που περιμένουν να υποβληθούν σε στεφανιογραφία συχνά ανησυχούν και αντιμετωπίζουν σημαντικά συναισθηματικά προβλήματα προεπεμβατικά, γεγονός που μπορεί να οδηγήσει σε αύξηση της αρτηριακής πίεσης, της καρδιακής συχνότητας, του αναπνευστικού ρυθμού και της ζήτησης οξυγόνου από το μυοκάρδιο. Οι περιβαλλοντικοί παράγοντες (ευχάριστοι ήχοι φύσης, φωτισμός ημέρας, ευχάριστα χρώματα) αποδείχτηκαν μέσα από μια τυχαιοποιημένη μελέτη ότι έχουν θετική επίδραση στους δείκτες άγχους που αντιμετωπίζουν οι ασθενείς περιμένοντας να υποβληθούν σε στεφανιαία αγγειογραφία 114. Αντίθετα, σε επικαιροποιημένη ανασκόπηση του Cochrane διαπιστώθηκε ότι στα άτομα με στεφανιαία νόσο, δεν υπήρχαν ενδείξεις ότι οι ψυχολογικές θεραπείες είχαν επίδραση στη συνολική θνησιμότητα, στις επιπλοκές των διαδερμικών επεμβατικών πράξεων ή στο ποσοστό μη θανατηφόρου εμφράγματος του μυοκαρδίου, αν και ο ρυθμός καρδιακής θνησιμότητας μειώθηκε και τα ψυχολογικά συμπτώματα όπως κατάθλιψη, άγχος ή στρες μετριάστηκαν.…”
unclassified